2014
DOI: 10.4049/jimmunol.1401655
|View full text |Cite
|
Sign up to set email alerts
|

T Cell–B Cell Thymic Cross-Talk: Maintenance and Function of Thymic B Cells Requires Cognate CD40–CD40 Ligand Interaction

Abstract: Thymic development requires bidirectional interaction or cross-talk between developing T cells and thymic stromal cells, a relationship that has been best characterized for the interaction between thymocytes and thymic epithelial cells (TECs). We have characterized here the requirement for similar cross-talk in the maintenance and function of thymic B cells, another population that plays a role in selection of developing thymic T cells. We found that maintenance of thymic B cells is strongly dependent upon the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 53 publications
2
29
0
Order By: Relevance
“…By contrast, an agonistic anti-CD40 antibody induced Airereporter expression and Aire mRNA transcription together with MHCII upregulation in B cells ( Figures 3A, 3B, and S3). In Cd40 -/-and Cd40lg -/-mice, thymic but not peripheral B cells were substantially diminished, consistent with CD40 signals controlling thymic B cell numbers ( Figure 3C; Fujihara et al, 2014). Most significantly, thymic B cells in these mice did not express Aire mRNA, had not undergone class-switching, and failed to upregulate CD80 ( Figures 3D-3F).…”
Section: B Cell Licensing Requires Cd40 Signalingmentioning
confidence: 51%
See 2 more Smart Citations
“…By contrast, an agonistic anti-CD40 antibody induced Airereporter expression and Aire mRNA transcription together with MHCII upregulation in B cells ( Figures 3A, 3B, and S3). In Cd40 -/-and Cd40lg -/-mice, thymic but not peripheral B cells were substantially diminished, consistent with CD40 signals controlling thymic B cell numbers ( Figure 3C; Fujihara et al, 2014). Most significantly, thymic B cells in these mice did not express Aire mRNA, had not undergone class-switching, and failed to upregulate CD80 ( Figures 3D-3F).…”
Section: B Cell Licensing Requires Cd40 Signalingmentioning
confidence: 51%
“…In addition to providing thymic B cells with enhanced APC features such as elevated MHCII and CD80, CD40 signaling was shown to also control the size of the thymic B cell pool, which in sum should quantitatively enhance the tolerogenic potential of the thymic B cell population as a whole (Fujihara et al, 2014). Importantly, our findings strongly suggest that besides these quantitative effects, intrathymic licensing is likely to have a substantial qualitative influence on the self antigen spectrum displayed by thymic B cells.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…All data shown are representative of three independent experiments. ***p < 0.001. development, the maintenance of thymic B cells requires CD40/ CD40L but not MHC class II interaction [48]. Hence, signals required for thymic Treg cell development are distinct from those required for thymic B cell maintenance.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, it has been shown that CD40L −/− mice have a 10x reduction in the total number of thymic B cells, suggesting this pathway may be important for the survival and maintenance of thymic B cells [28]. More recently it was demonstrated by Fujihara et al that CD40 is important for thymic B cell proliferation and function in a cell autonomous manner [29]. …”
Section: Thymic B Cell Activationmentioning
confidence: 99%